Search for dark matter and unparticles in events with a Z boson and missing transverse momentum in proton-proton collisions at ?s = 13 TeV (vol 9, 106, 2017) - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E. (Springer, 2018)
[Abstract Not Available]